EFEKTIVITAS PENGGUNAAN ALAT PERAGA DALAM MENINGKATKAN PEMAHAMAN SISWA PADA TEMA DIRIKU DI PAUD AL YUSRI - Anggreni (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2020)
Early childhood is a child who is born in a state of fitrah (pure) where early childhood is still innocent or does not know the difference between good and bad. This study was conducted to determine the effectiveness of using learning aids to improve student understanding on the theme of Myself at PAUD Al-Yusri, Simalungun Regency. This research is qualitative research, the method used in this research is descriptive analytical method and includes field research (Field study reseach) which is intended to study the background of the current situation and social interactions, individuals, groups, institutions related to learning the theme of Myself at PAUD Al-Yusri Simalungun Regency. In this study using observation, interview, and documentation methods. The results of this study indicate (1) The use of teaching aids in improving student understanding of the theme of Myself at PAUD Al-Yusri Simalungun Regency is very effective. (2) The supporting factors for teachers in the use of teaching aids to improve student understanding on the theme of Myself are teachers who have been able to master and use learning aids and teaching aids for the theme of Myself is simple so that it allows teachers to make it.